The association between diet and sleep with internalising symptoms in young athletes: a serial multiple mediation models - Gao, Yun; Wang, Lei (Frontiers in Nutrition, 2024)
This study examined the mediating effects of sleep quality on the relationship between dietary patterns and internalising symptoms in young athletes. The current crosssectional study involved 758 Chinese young athletes. The adapted Australian Athletes Diet Index was used to assess dietary patterns, and sleep was measured using the Athletes Sleep Screening Questionnaire. The Generalized Anxiety Disorder 7 scale and the Patient Health Questionnaire 9-item scale were used to assess symptoms of anxiety and depression. Structural Equation Modelling (SEM) analysis was used to examine the mediating role of sleep quality in young athletes. Raw scores of chronotypes, sleep quality, anxiety and depression were calculated for the statistical analysis. No significant indirect effects were found in adolescents. In adult athletes, diet mediated the relationship between chronotype and sleep quality (β = -0.028, p < 0.001). Sleep quality mediated the association between diet and anxiety (β = -0.060, p = 0.001), and depression (β = -0.076, p = 0.001). Additionally, diet and sleep quality mediated the association between chronotypes and anxiety (β = -0.028, p = 0.001), and depression (β = -0.028, p = 0.001). Sleep quality mediated the relationship between dietary patterns and internalising symptoms in young adult athletes. Additionally, diet and sleep quality mediated the association between chronotypes and internalising symptoms in young adult athletes.